A Model for the Estimation of Hepatic Insulin Extraction After a Meal - Piccinini, Francesca (IEEE Trans Biomed Eng, 2015)
GOAL: Quantitative assessment of hepatic insulin extraction (HE) after an oral glucose challenge, e.g. a meal, is important to understand the regulation of carbohydrate metabolism. The aim of the current study is to develop a model of system for estimating HE. METHODS: Seven different models, of increasing complexity, were tested on data of 204 normal subjects, who underwent a mixed meal tolerance test, with frequent measurement of plasma glucose, insulin and C-peptide concentrations. All these models included a two-compartment model of C-peptide kinetics, an insulin secretion model, a compartmental model of insulin kinetics (with model order ranging from one to three) and different HE descriptions, depending on plasma glucose and insulin. Model performances were compared on the basis of data fit, precision of parameter estimates and parsimony criteria. RESULTS: The three-compartment model of insulin kinetics, coupled with HE depending on glucose concentration, showed the best fit and a good ability to precisely estimate the parameters. In addition, the model calculates basal and total indices of HE (HE(b) and HE(tot), respectively), and provides an index of HE sensitivity to glucose (S(G)(HE)). CONCLUSION: A new physiologically-based HE model has been developed, which allows an improved quantitative description of glucose regulation. Significance: The use of the new model provides a in-depth description of insulin kinetics, thus enabling a better portrait of patient metabolic state.